Os Transportes individuais de passageiros nos centros sub-regionais: a regulamentação dos serviços de transporte público individual (táxi) e transporte remunerado privado individual de passageiros (aplicativos de mobilidade) no município de Paragominas - COSTA, Deryck Amaral da (2022)
The introduction of technological innovations has changed the way we execute various daily activities, such as requesting a transportation. Given this, the research about urban transport regulations is important, in order to verify how the municipalities, characterized as sub-regional centers, specifically Paragominas, regulate the individual public transport services (taxis) and private individual transport of passengers (ridesourcing services) and possible injuries to rights. Therefore, it is necessary to analyze the National Policy of Urban Mobility (NPUM), responsible for the study of limits and repercussions of individual transport and also verifies the provision and functioning of individual transport services in the Municipality of Paragominas. Thus, a bibliographical and documentary research was executed with scientific articles, news and legislation. Consequently, this paper conclude that the NPUM presents guidelines and concepts for transport in the municipalities, as well as technological innovations contribute to a competing market and the regulation of urban transport in sub-regional centers is under development or has failed, which confirms the finding that the absence of urban transport regulation in sub-regional centers causes damage to fundamental rights.